Diagnosis of onychomycosis by trypsin treatment method - Xess Immaculata; Dubey Deepti; Purva Mathur (Wolters Kluwer Medknow Publications, 2007)
Background: Fungal infection of the nails is a common, difficult to treat problem, prevalent worldwide. A discrepancy in the microscopic examination and culture findings can create problems in the diagnosis of this common infection. Aim: This study was designed to evaluate a new method for accurate diagnosis of onychomycosis. Materials and Methods: Nail samples from 25 patients of suspected onychomycosis were taken. A portion of the samples was treated with 2% trypsin before culturing and the rest was processed by the standard mycological technique. Results: A higher number of culture positive samples were obtained by the trypsin treatment method as compared to the standard technique. Conclusion: Trypsin treatment prior to culture increases the isolation of fungi from nail samples.